Sea Surface Salinity Signature of the Tropical Atlantic Interannual Climatic Modes. Issue 10 (21st October 2018) - Awo, F. M.; Alory, G.; Da‐Allada, C. Y.; Delcroix, T.; Jouanno, J.; Kestenare, E.; Baloïtcha, E.
Abstract: The characteristic sea surface salinity (SSS) patterns associated with the tropical Atlantic meridional and equatorial interannual modes are extracted from in situ observations, by a statistical analysis performed on the 1980–2012 period. These SSS signatures of the interannual climatic modes are reproduced in a regional numerical simulation. For each mode, oceanic and/or atmospheric processes driving the SSS signature are identified through a mixed‐layer salt budget in the validated model. During a positive meridional mode in spring, a northward shift of the Intertropical Convergence Zone and related precipitation maximum creates a south‐north dipole of positive‐negative SSS anomalies around the equator. Western boundary currents strengthen and advect relatively fresh equatorial waters, which creates negative SSS anomalies in the north and south west tropical Atlantic. Meridional and vertical advection create positive SSS anomalies off the Congo River. During a positive equatorial mode in summer, a southward shift of the Intertropical Convergence Zone‐related rainfall maximum creates a south‐north dipole of negative‐positive SSS anomalies between the equator and 10°N. Meridional advection also contributes to the positive SSS anomalies between 5°N and 10°N. Vertical advection and diffusion at the mixed‐layer base create positive SSS anomalies between 5°S and the equator. Horizontal advection creates large SSS anomalies in the North Brazil Current retroflection region, negative along the coast and positive further offshore. The SSS signatures of the meridional and equatorial modes described above are well captured by the Soil Moisture–Ocean Salinity satellite during the 2010 and 2012 events. Plain Language Summary: This study shows that both meridional and equatorial interannual climatic modes impact the sea surface salinity (SSS) in tropical Atlantic through atmospheric and/or oceanic processes. The atmospheric forcing, related to Intertropical Convergence Zone migration, controls the equatorial region, while the advection, due to modulation of current dynamics, vertical SSS gradient, and mixing at the base of mixed layer, drives SSS in the region under the influence of river plumes. Key Points: The SSS signature of the tropical Atlantic meridional and equatorial interannual modes is extracted from in situ observations Oceanic/atmospheric processes driving the signature of each mode are identified through a mixed‐layer salt budget in a validated model The SSS signatures of the meridional and equatorial modes are well captured by SMOS satellite during particular events